Rekonseptualisasi Manajemen Finansial Lembaga Pendidikan Islam Swasta:: Integrasi Nilai Hisbah dan Prinsipi Akuntabilitas Modern - Hairul Puadi (Universitas Al-Qolam Malang, 2025)
Islamic educational institutions (IEIs) in Indonesia, including madrasas and Islamic boarding schools (pesantren), face a profound paradox: they enjoy immense public trust yet are chronically trapped in an acute vicious cycle of financial instability. This study aims to re-conceptualize financial governance within IEIs by integrating traditional Islamic values—specifically hisbah (supervision)—with modern managerial accountability and transparency principles. Utilizing a qualitative-conceptual approach, this research analyzes the theological foundations of financial management in the Qur'an and Hadith alongside modern education funding frameworks. The study reveals that the widespread financial crises in IEIs stem from traditional-nepotistic appointments, inadequate budget diversification, and manual bookkeeping vulnerable to errors. To counter these vulnerabilities, this paper proposes an integrative governance model where the classical concept of hisbah is operationalized through digitalized accounting, systemic internal controls (separating authorizers, coordinators, and treasurers), and programmatic transparency. The novelty of this research lies in its practical synthesis, demonstrating how transcendental Islamic values are not merely ethical abstract concepts but can be concrete drivers for structural efficiency and modern public trust in educational institutions.